1996
DOI: 10.1148/radiology.199.1.8633131
|View full text |Cite
|
Sign up to set email alerts
|

Primary carcinoma of the lung overlooked at CT: analysis of findings in 14 patients.

Abstract: Endobronchial location and lower lobe predominance were the most common characteristics of overlooked lung cancer at CT. The presence of unrelated major abnormalities at CT may also have contributed to failure to diagnose the tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(35 citation statements)
references
References 0 publications
2
29
0
4
Order By: Relevance
“…White et al demonstrated that endobronchial location and lower lobe predominance were the most common characteristics of overlooked lung cancer on CT scan. 10 Patz et al described that non-enhanced CT thorax through adrenal gland is sufficient for successful staging and contrast-enhanced CT (CECT) thorax did not substantially alter the tumor staging. 11 However, in this study CECT was done in majority of the patients to differentiate necrotic part of the tumor through which biopsy should be avoided and it was helpful in distinguishing central partially obstructing endobronchial mass from more distal collapsed or consolidated lung.…”
Section: Discussionmentioning
confidence: 99%
“…White et al demonstrated that endobronchial location and lower lobe predominance were the most common characteristics of overlooked lung cancer on CT scan. 10 Patz et al described that non-enhanced CT thorax through adrenal gland is sufficient for successful staging and contrast-enhanced CT (CECT) thorax did not substantially alter the tumor staging. 11 However, in this study CECT was done in majority of the patients to differentiate necrotic part of the tumor through which biopsy should be avoided and it was helpful in distinguishing central partially obstructing endobronchial mass from more distal collapsed or consolidated lung.…”
Section: Discussionmentioning
confidence: 99%
“…White et al (47) described location, shape and cell type of 15 lung cancers overlooked at CT and observed that the majority of these cancers had endobronchial location with lower lobe predominance. Gurney et al (48) documented nine lung tumors missed at CT, five of which were peripheral and four were central.…”
Section: Factors Leading To Missed Lung Cancer On Chest Ctmentioning
confidence: 99%
“…high sensitivity-is underscored by the fact that many failures in lung cancer diagnosis are due to errors of detection rather than interpretation. 19,20 Therefore, based on our initial data, we could not conclude that radiographers were suitable to act as first readers in CT lung cancer screening. This is because we found that radiographer sensitivity in the majority of cases was statistically significantly lower than that of the radiologists reading the same CTs.…”
Section: Discussionmentioning
confidence: 89%